PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) - Dewi, Ni Luh Putu Puspita; Noviari, Naniek (E-Jurnal Akuntansi; Vol 21 No 2 (2017), 2017)
Tax is a sector that plays an important role in the economy, because in the post revenue of the State Budget (APBN) tax contribution has a larger portion compared to other sources of income (non-tax). Tax revenues in Indonesia have not been maximized, whereas Indonesia has high tax revenue potential due to the large population and business activities. Tax evasion is a series of tax planning activities. Tax evasion can be said to reduce taxes by following existing regulations. The issue of tax avoidance is complicated and unique, on the one hand tax evasion is allowed, but on the other hand tax avoidance is undesirable. This study aims to determine the effect of firm size, leverage, profitability and corporate social responsibility on tax avoidance. Tax evasion in this study is proxyed by CETR value. The data used is secondary data. The population of this study is the Indonesia Stock Exchange (IDX) during the period 2013-2015. The method of determining the samples from this study is by purposive sampling in accordance with predetermined criteria and obtained sample of 36 companies. The analysis technique used is multiple linear regression. Based on the results of multiple linear regression analysis, the research shows that firm size, leverage and corporate social responsibility disclosure have a negative and significant effect on tax avoidance, while profitability has positive and significant effect on tax avoidance. Keywords: tax evasion, firm size, leverage, profitability, corporate social responsibility disclosure.